Integrating gender into Kenya’s evolving seed policies and regulations for roots and tubers - Sulle, E.; Mudege, Netsayi N. (International Potato Center, 2021)
In many developing countries where farmers grow vegetatively propagated crops (VPCs), they are often unable to increase on-farm productivity partly due to limited access to quality seeds. Yet, seed policy and legal frameworks for VPCs in many countries show a limited consideration of the specific characteristics of the seed systems for root, tuber and banana crops. Moreover, there is a lack of understanding of how the implementation of current seed policy frameworks affect participation by men and women as either seed producers or seed users. This paper examines the Kenyan seed policy processes and discusses the gender-sensitivity of how seed policy decisions are made in order to understand how these can be made gender sensitive. It unpacks the context in which seed policies are implemented; how the content of seed policies can differently affect men and women farmers’ participation in seed production and access to seed; and provides recommendations on how seed policy can be made more inclusive. In many developing countries where farmers grow vegetatively propagated crops (VPCs), they are often unable to increase on-farm productivity partly due to limited access to quality seeds. Yet, seed policy and legal frameworks for VPCs in many countries show a limited consideration of the specific characteristics of the seed systems for root, tuber and banana crops. Moreover, there is a lack of understanding of how the implementation of current seed policy frameworks affect participation by men and women as either seed producers or seed users. This paper examines the Kenyan seed policy processes and discusses the gender-sensitivity of how seed policy decisions are made in order to understand how these can be made gender sensitive. It unpacks the context in which seed policies are implemented; how the content of seed policies can differently affect men and women farmers’ participation in seed production and access to seed; and provides recommendations on how seed policy can be made more inclusive.